Models of network reliability : analysis, combinatorics, and Monte Carlo /: analysis, combinatorics, and Monte Carlo. ([2012]) - Gert︠s︡bakh, I. B (Ilʹi︠a︡ Borukhovich); Shpungin, Yoseph
No abstract available